Green innovations in urban landscape: opportunities to use Slovakia's experience - N. V. Maksymenko; M. Bihuňová (Людина і довкілля: Проблеми неоекології)
Purpose.  To analyze the results of an internship at the Slovak Agricultural University in Nitra, which was aimed at studying the possibility of introducing green industrial innovations into urban landscapes under the project of the International Visegrad Fund "Green Innovations in Urban Landscape Ecology".